A WOOD FROM THE EARLY CRETACEOUS OF JAMES ROSS ISLAND,ANTARCTICA (Ameghiniana, 2014)
An Early Cretaceous (Albian) wood is described as Agathoxylon sp. A from James Ross Island, Antarctica. This species displays distinct growth rings, 1-2 seriate, araucarioid pitting on radial walls of tracheids, uniseriate to partly biseriate rays, 1(9)25 cells high, and 1-4 mainly araucarioid pits in crossfield. The material provides new data on the characterization of Cretaceous coniferous dominated forests of Antarctica.